Methods for in vitro CRISPR/CasRx-Mediated RNA Editing - Chuang, Yu-Fan; Wang, Peng-Yuan; Kumar, Satheesh; Lama, Suraj; Lin, Fan-Li; Liu, Guei-Sheung (Frontiers in Cell and Developmental Biology, 2021)
Specific changes in the genome have been accomplished by the revolutionary gene-editing tool known as clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system. The advent of programmable RNA editing CRISPR/Cas nucleases has made this gene-editing tool safer and more precise. Specifically, CasRx, a family member of the Cas13d family, has shown great therapeutic potential. Here, we describe the in vitro methods of utilizing this powerful RNA editing platform and determine the RNA editing efficiencies for CasRx with different forms of guide RNAs (also known as gRNA or sgRNA).